Breastfeeding Of Shift Working Mothers: a Qualitative Study - Sari, Rina Puspita; Adawiyah, Siti Robeatul (UIMA Press, 2021)
Introduction: Working mother has a dual role as a worker and caring for children including the fulfillment of breastfeeding (infants aged 0-24 months). The shift work method has the risk of fatigue and stress thus affect milk production. The shift work method requires working mother to have more effective time management for direct breastfeeding and pumping breast milk. Objective: Obtain a description of breastfeeding experience of shift working mother. Method: The phenomenological approach was used in this qualitative research. Selection of participants using a purposive sampling method of 8 people. In-depth interviews were used in data collection and then analyzed using Colaizzi's method. Results: The qualitative thematic analyses included the following: (1) breastfeeding motivation of shift working mother, (2) problem occurs of breastfeeding period of shift working mother, 3) shift working mother strategic to resolve the problems, and (4) source and form of supports. Conclusion: The support needed by working mothers is flexible time for breastmilk pumps, comfortable lactation rooms, consistent shift schedule arrangements, and assistance from occupational health nurses in companies. The results of this study can be used as the basis for occupational health providing nursing interventions such as education, counseling and advocacy to management.